The City of London in the Asian crisis - Clark, G; Wójcik, D (Oxford University Press, 2001)
This paper seeks to understand the Asian crisis through the eyes of the City of London. Relying upon material provided by The Financial Times (FT), we construct an index of pessimism to chart the dominant City of London interpretation of the path of the crisis. This index is set against data on the actual performance of the Hong Kong, and Tokyo, London, and New York stock markets over the same period. We have the luxury of retrospectively reconstructing the actual path of the crisis whereas the FT (and global financial markets) had to respond to specific events in a chain of apparent cumulative events. Our goal is to explain the construction of the dominant pessimistic interpretation of the path of the crisis, placing the City of London in the context of global markets (in time, between Tokyo and New York). In the penultimate section of the paper we report on an interview with Riley, the FT columnist, about the results of our analysis, emphasizing the apparent homogeneity of information and opinion in the City of London as opposed to New York. The conclusion focuses upon the implications of this argument for the study of discontinuities between global markets, and the future of financial centres.